Fisetin Inhibits Osteogenic Differentiation of Mesenchymal Stem Cells via the Inhibition of YAP - Chanchao Lorthongpanich; Thanapon Charoenwongpaiboon; Prapasri Supakun; Methus Klaewkla; Pakpoom Kheolamai; Surapol Issaragrisil (MDPI AG, 2021)
Mesenchymal stem cells (MSCs) are self-renewal and capable of differentiating to various functional cell types, including osteocytes, adipocytes, myoblasts, and chondrocytes. They are, therefore, regarded as a potential source for stem cell therapy. Fisetin is a bioactive flavonoid known as an active antioxidant molecule that has been reported to inhibit cell growth in various cell types. Fisetin was shown to play a role in regulating osteogenic differentiation in animal-derived MSCs; however, its molecular mechanism is not well understood. We, therefore, studied the effect of fisetin on the biological properties of human MSCs derived from chorion tissue and its role in human osteogenesis using MSCs and osteoblast-like cells (SaOs-2) as a model. We found that fisetin inhibited proliferation, migration, and osteogenic differentiation of MSCs as well as human SaOs-2 cells. Fisetin could reduce Yes-associated protein (YAP) activity, which results in downregulation of osteogenic genes and upregulation of fibroblast genes. Further analysis using molecular docking and molecular dynamics simulations suggests that fisetin occupied the hydrophobic TEAD pocket preventing YAP from associating with TEA domain (TEAD). This finding supports the potential application of flavonoids like fisetin as a protein-protein interaction disruptor and also suggesting an implication of fisetin in regulating human osteogenesis.